Hematopoietic cell transplantation for Langerhans histiocytosis - Zamperlini Netto, Gabriele; Bom , Ana Paula Kuczynski Pedro (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2026)
Langerhans cell histiocytosis is a rare myeloid neoplasm that primarily affects children. Initial treatment depends on risk stratification, but overall survival is excellent. Patient with high-risk disease with risk organ involvement can experience disease reactivation or refractoriness to front-line therapy. A standard approach is not established in the literature, with different reported strategies, including conventional chemotherapy, MAPK-inhibitors and allogeneic hematopoietic (HCT). Allogeneic HCT is supported by retrospective studies with overall survival ranging from 56 to 77% in the largest series. Disease status at the time of HCT and the conditioning regimen (reduced-intensity conditioning versus myeloablative conditioning) correlates with survival and toxicity. Most recently, reduced-intensity conditioning modality has emerged as the preferred option for patients diagnosed with Langerhans cell histiocytosis who require allogeneic HCT.